Enhancing Employee Performance: The Impact of Engagement, Job Rotation, Compensation, and Motivation - Lestari, Dwi Ayu; Deviastri, Lily (Human Capital and Organizations, 2024)
This research aims to determine the influence of employee engagement, transfers, compensation and motivation on employee performance. Apart from that, you can see the review from an Islamic perspective. The population of this study were employees of the Jakarta Cakung Primary Tax Service Office with a sample size of 89 respondents. The sampling technique uses a non-probability sampling method, with a saturated sampling technique through distributing questionnaires. The data analysis method uses the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The model in this research provides a strong influence with a strong level of relevance in predicting the influence between variables with a large level of suitability. employee engagement has a positive and significant effect on employee performance. Furthermore, mutations have a positive and significant effect on employee performance. Compensation has a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance. Managerial Implications Organizations should prioritize enhancing employee engagement through effective communication and involvement in decision-making processes to boost performance. Additionally, strategic employee mutations or transfers can be leveraged to match skills with job roles more effectively. Fair and competitive compensation packages are essential to motivate employees and enhance their commitment.